Ujaran Kebencian Pada Kolom Komentar Channel Hot Shot Pada Youtube SCTV - Asrul Nur Iman; Anissya Nofi Rachmawati (Journalism, Public Relation and Media Communication Studies Journal (JPRMEDCOM), 2023)
On YouTube, users can freely comment on various posts, making it a widely used social media platform. However, this feature can also lead to instances of hate speech and inappropriate language. A recent study aimed to analyze such instances of hate speech within the comments section of the Hot Shot account on YouTube SCTV. Specifically, the study examined the news content titled 'Exciting! Lesti Kejora Officially Reports Rizky Billar on Allegations of Domestic Violence. The researchers used a qualitative approach with a descriptive method and identified six comments that fell into the category of hate speech. These comments were found to be insulting and intimidating, such as 'Once domestic violence will always be domestic violence', 'No thanks', and 'Who is Lesti? God?'. Certain words used in the comments were found to promote hate speech, including 'human' and 'trash'. Such comments can have a negative impact on the individuals they are directed towards and perpetuate a culture of hate speech. Keywords: comment column, top comment, perlocutionary speech act, hate speech, YouTube.